THE REVIEW OF BIOCHEMISTRY ASPECTS OF MOCAL (MODIFIED CASSAVA FLOUR) PROCESS WITH SPONTANEOUS FERMENTATION - Yudi Cristian Windartha (UPT Penerbitan Universitas Jember, 2012)
Cassava, also known as Manioc, and the Latin name is Manihot esculenta, is aannual tropical and sub – tropical plant derive from the family of Euphorbiaceae. Thetuber is known as a staple food – producing carbohydrate, and its leaves can be made as avegetable. In food industry, Cassava can be used to make cassava flour or tapioca for food.MOCAL is cassava flour that in production process through spontaneous fermentation.Biochemical changing takes place during the fermentation. This produces a bettercharacteristic of modified MOCAL, so it can be used in a larger food industry. Theapplication of MOCAL in the food industry has been applied, but a scientific study aboutthe fermentation process of MOCAL has not been conducted. A scientific study about thebiochemical changing during the fermentation process of MOCAL is needed. This researchis an observation toward the biochemical changing of MOCAL. The basic ingredient iscassava varieties Paroka. It is obtained directly from the farmers in Lumajang. The cassavais about 7 – 9 months old. The research is conducted at Laboratory of Chemistry andBiochemical food product, department of agriculture product technology, Faculty ofAgricultural technology, University of Jember. It began Mei 2007 until Mei 2008. In itsdesign, MOCAL is produced in various time of fermentation process (0, 6, 24, 30 and 48hours), then continues to analyze the biochemistry of MOCAL immersion water.Analyzing of the data uses descriptive methods. The result is shown in table, and graph orhistogram is made to ease the data interpretation. The result of the research showsbiochemical changing because of microbe activity and carbohydrate breaker enzymesduring the fermentation process. The pH of the MOCAL water immersion decreases duringthe fermentation because of organic acids which is produced by the microbe during thefermentation process. The turbidity of MOCAL water immersion increases. It indicates theincreasing amount of microbe during the fermentation process. During the fermentationprocess, the microbes produce enzymes that increase the amount of soluble protein. Theactivity of the carbohydrate – breaker enzymes such as cellulose and amylase in breakingcellulose increases during the fermentation process. These activities affect the texture ofcassava chip which shows softening during the fermentation process.